Developing hierarchical standardized home care nursing statements using nursing standard terminologies. (September 2020) - Lee, Jinhwa; Kang, Min-Jeoung; Garcia, Jose P.; Dykes, Patricia C.
Highlights: Home care nursing records were highly mapped to nursing standard terminologies. Nursing standards with different levels of granularity were aligned to form a hierarchical standardized statement structure. The hierarchical structure can capture both abstract and detailed nursing documentation information. Abstract: Objectives: Home care nursing requires high quality documentation to facilitate communication between health providers. Despite the awareness surrounding the importance of documentation, the home care nursing environment lends itself to incomplete and inaccurate documentation. Our study aims to develop a hierarchical standardized home care nursing statement (S-HCNS) structure that can increase documentation quality and completeness. Methods: We collected a year of home care nursing notes from a hospital-based home care nursing agency in South Korea. Two nursing terminology standards, the International Classification for Nursing Practice (ICNP) and the Clinical Care Classification (CCC), were used to develop the hierarchical S-HCNS structure. Results: A total of 1, 230 S-HCNSs were derived by mapping 61, 061 home care nursing notes to the ICNP. Among the total statements, 82.8 % were completely mapped and 0.3 % were not mapped. A total of 99.2 % of the S-HCNSs were classified within the CCC system to build a hierarchical S-HCNS structure. Conclusions: The ICNP and CCC showed high mapping rates when building the hierarchical S-HCNSs. The unmapped concepts did not exist in the CCC or ICNP but existed in other terminology systems such as SNOMED CT. The differences in granularity between the two terminology standards enabled the development of a hierarchical structure, which enabled the representation of the appropriate level of detail found within clinical documentation. We expect this structure will increase documentation quality and completeness.